Essential Occupational Safety and Health Interventions for Low- and Middle-income Countries: An Overview of the Evidence - Jos Verbeek; Ivan Ivanov (Elsevier, 2013)
There is still a considerable burden of occupational diseases and injuries in the world. It is not well known which interventions can effectively reduce the exposures at work that cause this burden. The objective of this article is to summarize evidence from systematic reviews of interventions to prevent occupational diseases and injuries. We included systematic reviews of interventions to reduce the incidence of work-related cancer, dust-related diseases, occupational asthma, chronic obstructive pulmonary disease, noiseinduced hearing loss, back pain, and occupational injuries. We searched Medline and Embase with predefined search strategies to locate systematic reviews of these interventions. We found 23 systematic reviews of which the results are also applicable to low- and middle income countries. Effective measures to reduce exposure leading to work-related cancer, dust-related diseases, asthma, chronic obstructive pulmonary disease, noise, and injuries are available. However, better implementation of these measures is needed. Regulation, enforcement of regulation, and incentives for employers are effective interventions to achieve this goal. There is evidence that feedback and rewards for workers help in reducing occupational injuries. There is no evidence in many studies that back pain can be prevented. Personal protective equipment technically has the potential to reduce exposure but this is difficult to put into effect. There is no evidence in the studies regarding the effectiveness of education and training, preventive drugs, or health examinations. There is evidence that the implementation of technical measures enforced by regulation can prevent occupational diseases and injuries. For other interventions such as education or health examinations, there is no evidence that supports their effectiveness. More systematic reviews are needed in the area of injury prevention.